Judging Filipino intellect traits desirability and controllability in evaluating the self and others - Garcia, John Addy Sapalo (2007)
To fully understand the salience of trait evaluation to self-knowledge, there is a need to investigate the process through a socio-psychological perspective of motivated social cognition. The study is a three-phased concurrent triangulated (QUAN-qual) research which investigated the relationship between trait desirability and controllability and how college students make trait judgment about themselves, and how professors evaluate traits of students. Students generally considered all the Filipino intellect traits to be desirable and controllable. The correlation data showed that trait desirability was positively related with both self-evaluation and evaluation of others, and that trait controllability was positively correlated only with self-evaluation.
"January 2007."
Thesis (Ph.D. Education : Educational Psychology)--University of the Philippines, Diliman.
Keywords: Intellect; Self-evaluation -- Philippines